Discriminação de espécies florestais com a utilizaçao da razão isotópica 13 C e 15 N e espectroscopia no infra-vermelho próximo (FT-NIRs)) - Durgante, Flávia Machado (Instituto Nacional de Pesquisas da Amazônia - INPA, 2011)
The combined use of high technology instruments and appropriate techniques for discriminating tree species isnecessary to improve the biodiversity inventory system in tropical countries. This study was carried out to verify the performance of C and N isotopes ratios, the total leaf concentration values of C and N (%) and near-infrared spectroscopy readings as indicators to discriminate eight species of Eschweilera and two of Corythophora of the Brazilian Amazon. It was observed that the isotopes analysis and the leaf N and C concentrationswere not reliable enough to discriminate the studied species. However, the near infrared spectroscopy (FT-NIRS) presented an outstanding performance; therefore, it seems to be a promising tool to improve tree species discrimination system. Utilizing thirty-six spectral readings to represent an individual, we obtained 99.4% of correct species discrimination. When only one spectral reading from any part of the leaf was used, the correct discrimination reached 97.1 %.In the near future, a portable FT-NIRS, for instance, could be used in forest inventory data collection. The only requirement is the memory feeding, which should be done using the most reliable and consistent botanical identification of the most abundant Amazonian tree species. This process should be refined over time with the feedback from new inventories. By any means, the use of FT-NIRS has demonstrated that it is much more reliable than the rule of thumb highly practiced for tree identification during forest inventory carried out in the Brazilian Amazon.
Keywords: Amazoniana; Espectroscopia no infra vermelho; Lecythidaceae